Tingkat Pengetahuan Masyarakat Tentang Penanganan Henti Jantung di Wilayah Jakarta Utara: Level of Community Knowledge about Cardiac Arrest Management in North Jakarta - Rahma Hidayati (Fakultas Keperawatan Universitas Andalas, 2020)
Cardiac Arrest is one of the most common conditions of emergency in the public. First aid from first responder can prevent the risk of death and disability. The public knowledge in handling the emergency on cardiac arrest is necessary to investigate because knowledge is the basis for taking action. Many incidents of cardiac arrest in the community that cannot be saved because of their ignorance to provide emergency response. This research aims at identifying the public knowledge in the handling of cardiac arrest emergency . This research applies an analytical-descriptive method with number of respondents involved of 250 persons selected randomly based on a cluster sampling technique. The data collected uses a questionnaire and analysis with a Univariate and bivariate Statistics. The results shows that 55.6 % respondents have low knowledge on handling the cardiac arrest emergency. There was a significant relationship between level of knowledge with education level, sources information and BLS training experience. Within the interval estimation of 95%, the respondent’s knowledge varies from 13.48 to 14.07 (low). Further research can be done by additional the region coverage and developing aspects of BLS attitudes and skills.